If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1m = 17 Solving 2 + -1m = 17 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1m = 17 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 17 + -2 -1m = 17 + -2 Combine like terms: 17 + -2 = 15 -1m = 15 Divide each side by '-1'. m = -15 Simplifying m = -15
| -2.7+3.6=-5.8x+0.5 | | X+1-2x=-1 | | 9b-36=15b-10 | | -4x=6 | | -1=3x+2x+4 | | -2(8n+4)=104 | | 2g=5(3g+1) | | 3y^2-10y+3= | | -9+2x+7x=54 | | 9x-13=20x+20 | | (5x-69)(5x+27)= | | (p/7)-0.5=1.3 | | 6z=8z-18 | | -(2-x)-3(6+8x)-12=0 | | -15=-4x+2x+1 | | x^3-6x^2+8x+2=0 | | 1.5(8-6x)=x | | -4.5=1.2k | | -v-15=-6v+5 | | 2x-5=6x+4x-4 | | -33=7x+6x+6 | | 3=3/4(-4)+b | | -6x-(1+5x)=-5 | | 2x-7+5x-3+2x-2= | | 3a+1=-3.6(a-5) | | 0.6+(-4a)=-1.4 | | 3(c)-4(c)+1=5(c)+2+3 | | 4+3x+x=-24 | | 9x+9=9(x+4) | | 4x^2+4x-51=0 | | 2.6x+18=2.4x+222 | | 6x+15-5x=-3-10 |